环形振荡器电路 (2025)
本公开的各实施例涉及环形振荡器电路。在一个实施例中，环形振荡器电路包括：耦合在振荡器供电电压节点和基准电压节点之间的级联耦合反相器级的链，振荡器供电电压节点被配置为提供振荡器供电电压；耦合在振荡器供电电压节点和系统供电电压节点之间的电流发生器电路，系统供电电压节点被配置为提供系统供电电压，电流发生器电路被配置为将电流注入到振荡器供电电压节点中；以及偏置电路，包括串联耦合在基准电压节点和振荡器供电电压节点之间的第一偏置控制晶体管和第二偏置控制晶体管，其中第一偏置控制晶体管被配置为：响应于振荡器控制信号指示环形振荡器电路处于非活动操作状态，选择性地耦合基准电压节点和振荡器供电电压节点。 A ring oscillator (50) comprises a chain of inverters (52) coupled between an oscillator supply node (54) and a reference node (56), and a current generator (58) coupled between the oscillator supply node and a system supply node (60) and configured to inject a current (IOSC) into the oscillator supply node. Each inverter comprises a first (NF) and a second (NL) low-side transistors coupled in series between the reference node and an output node of the inverter, and a first high-side transistor (PF1) coupled between the oscillator supply node and the output node of the inverter. The first low-side transistor and the first high-side transistor have respective control terminals coupled to an input node of the inverter to